EFFECTIVENESS OF REGISTRATION OF MICRO AND SMALL BUSINESS LIMITED LIABILITY COMPANIES AFTER THE ENTRY INTO FORCE OF GOVERNMENT REGULATION NUMBER 8 OF 2021 - Heriyanti Heriyanti; Elvira Fitriyani Pakpahan; Lenny Maria Aritonang (Magister Kenotariatan Universitas Pasundan, 2022)
The government established a Draft Law cipta Kerja has the aim of making it easier for businesses in Indonesia to set up their businesses.This draft law is one of the urgency that is expected to be a barometer increase in the business world where Indonesia is still fifth in ASEAN.This is what makes the government always make regulations so that the community is easier in setting up its business, especially for Micro and Small Businesses.The Work Copyright Bill contains many additional rules, especially those related to the founder of a business entity.One of the things that is considered by the government to facilitate the community in setting up a business is by forming a new type of business entity, namely Individual Limited Liability Company (Micro and Small Business) that can be established only by 1 (one) person.With the hope that it can make it easier for businesses, especially micro and small businesses in setting up their businesses by facilitating the terms and minimizing capital.